Model Prediksi Perilaku Pencegahan Anemia dan Kekurangan Energi Kronis Pada Wanita Usia Subur di Kabupaten Serang - Metty Supyanti; Vivi Silawati; Siti Syamsiah; Rukmaini Rukmaini (Malahayati Nursing Journal, 2026)
ABSTRACT Anemia and chronic energy deficiency (CED) among women of reproductive age (WRA), particularly during pregnancy, remain significant public health problems in Indonesia, including Serang Regency, where the prevalence of anemia among pregnant women reaches 72.5%. This study aimed to develop a predictive model of anemia and chronic energy deficiency prevention behavior among women of reproductive age who are married, not currently pregnant, have previously experienced pregnancy, and plan future pregnancies in Serang Regency.This study employed a mixed-methods approach using a sequential exploratory design. The qualitative phase was conducted through in-depth interviews, observations, and document reviews involving women of reproductive age, health workers, and community health volunteers to explore factors influencing anemia and chronic energy deficiency prevention behaviors. The quantitative phase was conducted using a questionnaire survey involving 308 respondents selected through stratified random sampling. Data were analyzed using univariate, bivariate, and multiple linear regression analyses. The results showed significant relationships between knowledge, attitudes, family support, the role of health workers, and access to health services with anemia and chronic energy deficiency prevention behavior among women of reproductive age (p 0.05). Multivariate analysis showed that knowledge, attitudes, family support, the role of health workers, and access to health services simultaneously had a significant effect on anemia and chronic energy deficiency prevention behavior among women of reproductive age. The most dominant variable influencing prevention behavior was respondents’ attitudes. Anemia and chronic energy deficiency prevention behavior among women of reproductive age in Serang Regency is influenced by both individual and environmental factors. The developed predictive model demonstrated substantial contributions from the examined variables. Appropriate health education and adequate social support were found to be effective in promoting preventive behaviors and may serve as a basis for more effective interventions to reduce the risk of anemia and chronic energy deficiency. Keywords: Anemia, Self-efficacy, Chronic Energy Deficiency, Prevention Behavior, Women of Reproductive Age.  ABSTRAK Anemia dan kekurangan energi kronik (KEK) pada wanita usia subur (WUS), terutama selama masa kehamilan, merupakan masalah kesehatan yang signifikan di Indonesia, termasuk di Kabupaten Serang, di mana prevalensi anemia pada ibu hamil mencapai 72,5%. Penelitian ini bertujuan untuk mengembangkan model prediksi perilaku pencegahan anemia dan KEK pada Wanita Usia Subur sudah menikah, tidak sedang hamil, pernah hamil dan ingin merencanakan kehamilan kembali di Kabupaten Serang. Penelitian ini menggunakan pendekatan mixed methods dengan model sequential exploratory design. Tahap kualitatif dilakukan melalui wawancara mendalam, observasi, dan studi dokumentasi terhadap WUS, tenaga kesehatan, dan kader posyandu, untuk menggali faktor-faktor yang mempengaruhi perilaku pencegahan anemia dan KEK. Tahap kuantitatif dilanjutkan dengan survei menggunakan kuesioner kepada 308 responden, yang dianalisis menggunakan analisis univariat, bivariat, dan regresi linier berganda. Hasil penelitian menunjukkan bahwa terdapat hubungan yang bermakna antara pengetahuan, sikap, dukungan keluarga, peran tenaga kesehatan, dan akses pelayanan kesehatan dengan perilaku. Pencegahan anemia dan KEK pada Wanita Usia Subur (p0.05). Hasil analisi multivariat menunjukkan bahwa pengetahuan, sikap, dukungan keluarga, peran tenaga Kesehatan, dan akses pelayanan kesehatan secara simultan berpengaruh signifikan terhadap perilaku pencegahan anemia dan KEKpada Wanita Usia Subur, dengan variabel yang paling dominan mempengaruhi perilaku pencegahan anemia dan KEK Adalah sikap reponden. Bahwa perilaku pencegahan anemia dan KEK pada wanita usia subur di Kabupaten Serang dipengaruhi oleh faktor individu dan faktor lingkungan. Model prediksi yang dikembangkan menunjukkan kontribusi penuh dari variabel yang diuji. Edukasi yang jelas dan dukungan sosial yang memadai terbukti efektif dalam mendorong perilaku pencegahan, sehingga dapat menjadi dasar untuk intervensi yang lebih efektif dalam menurunkan risiko anemia dan KEK. Kata Kunci: Anemia, Efikasi Diri, Kekurangan Energi Kronik, Perilaku Pencegahan, Wanita Usia Subur.